From head to toes how your body works - Packard, Mary; Leder, Dora. (New York Simon & Schuster, 1985)
Describes different parts of the body including the circulatory, digestive, nervous, and reproductive systems, and explains how they work.
Keywords: Anatomy, Human -- Juvenile literature; Anatomy, Human; Body, Human -- Juvenile literature; Body, Human